(untitled) (Journal of the College of Basic Education, 2025)
This research aims to know (the effect of using imagination in acquiring scientific concepts for fifth-grade primary school students in the science subject and their problem-solving skills). To achieve this, the researcher selected a sample of (68) fifth-grade primary school students at the (alqstal) School affiliated with the Directorate of Education ., with (33) students for the experimental group and (35) students for the control group. The researcher rewarded the students of the two research groups in the variables of chronological age calculated in months and the academic achievement of the parents, the intelligence test, and the pre-problem-solving test. After the researcher identified the scientific material, the researcher identified (37) main and sub-concepts and formulated (111) behavioral objectives. The researcher prepared model teaching plans for each of the topics specified for the experiment. In order to measure the acquisition of scientific concepts and problem-solving among the students of the two research groups, the researcher prepared two tests: the first was a concept acquisition test, the number of its items was (33) Test paragraphs were verified for their validity and reliability, and the problem-solving test consisted of (25) paragraphs, the validity and reliability of which were verified. After applying the two research tools and statistically analyzing the results obtained by the researcher, the results showed that the experimental group outperformed the control group in the two tests: concept acquisition and problem-solving. The researcher also concluded that the imagination strategy is effective in acquiring concepts and solving problems among fifth-grade primary school students in science, compared to the traditional method. This is an important goal advocated by all modern educational conferences and literature. She recommended benefiting from the results of the current study by moving away from old teaching methods in teaching science.